1989
DOI: 10.1002/1520-6807(198901)26:1<78::aid-pits2310260111>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

WISC-R examiner errors: Cause for concern

Abstract: While errors on the WISC‐R are conceived primarily in terms of internal consistency and stability over time, examiners make mistakes that contribute to the inaccuracy of test scores. Studies to date mainly have investigated general scoring errors, rather than specific items most prone to error. Investigation of graduate students' test protocols indicated numerous scoring and mechanical errors that influenced the Full Scale IQ scores on two‐thirds of the protocols. Particularly prone to error were Verbal subtes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 10 publications
3
36
0
Order By: Relevance
“…Most literature has identified facets of scoring involving subjective judgment as a greater source of error than mechanical or arithmetic operations (Boehm, Duker, Haesloop, & White, 197 4;Miller & Chansky, 1972;Slate & Chick, 1989;Slate & Jones, 1990;Slate, Jones, & Murray, 1991 ). Accordingly, corrective suggestions focus primarily on the subjective elements, such as practice or special training and instructor feedback programs designed to ensure more uniformity in scoring (Blakey, Fantuzzo, Gorsuch, & Moon, 1987;Boehm et al, 1974;Connor & Woodall, 1983;Slate et al, 1991 ).…”
Section: III Scoring Error On Cognitive Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most literature has identified facets of scoring involving subjective judgment as a greater source of error than mechanical or arithmetic operations (Boehm, Duker, Haesloop, & White, 197 4;Miller & Chansky, 1972;Slate & Chick, 1989;Slate & Jones, 1990;Slate, Jones, & Murray, 1991 ). Accordingly, corrective suggestions focus primarily on the subjective elements, such as practice or special training and instructor feedback programs designed to ensure more uniformity in scoring (Blakey, Fantuzzo, Gorsuch, & Moon, 1987;Boehm et al, 1974;Connor & Woodall, 1983;Slate et al, 1991 ).…”
Section: III Scoring Error On Cognitive Testsmentioning
confidence: 99%
“…Additionally, various researchers, who have studied scorer training programs have concluded that errors persist because of "carelessness," especially in clerical operations (Miller & Chansky, 1972;Slate & Chick, 1989;Slate, et al, 1991 ). Researchers, stymied by their efforts to rectify careless errors, have suggested using computer scoring programs (Johnson & Candler, 1985) or double-checking scoring (Miller & Chansky, 1972;Slate & Hunnicutt, Jr., 1988).…”
Section: Iiill Review Of Scoring Error Factorsmentioning
confidence: 99%
“…Secondly, this study did not evaluate the relative ''difference'' in scores obtained by the RSCs versus the NOCL. Although scoring errors were not reported to significantly impact overall scores (Belk et al, 2002;Van Noord & Prevatt, 2002), corrected scores altered final scores in over 75% of the tests evaluated to date (Belk et al, 2002;Slate & Chick, 1989;Slate & Jones, 1990;Slate, Jones, & Murray, 1991;Slate, Jones, Murray, & Coulter, 1993). A majority of these studies did not find ''significant'' clinical interpretation changes related to the altered scores, but continued analysis of overall change is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have revealed that the Vocabulary, Comprehension, and Similarities subtests appear to be especially difficult for in-training graduate student examiners to interpret and score. According to Slate and Chick (1989), incorrect point assignment on these three subtests was a frequent error as was inappropriate questioning. Another common error was a failure to record the examinee's response in a verbatim manner.…”
Section: Scoring Errorsmentioning
confidence: 99%